Application of a Highly Selective Cathepsin S Two-step Activity-Based Probe in Multicolor Bio-Orthogonal Correlative Light-Electron Microscopy - van Dalen, Floris J.; Bakkum, Thomas; van Leeuwen, Tyrza; Groenewold, Mirjam; Deu, Edgar; Koster, Abraham J.; van Kasteren, Sander I.; Verdoes, Martijn (Frontiers in Chemistry, 2021)
Cathepsin S is a lysosomal cysteine protease highly expressed in immune cells such as dendritic cells, B cells and macrophages. Its functions include extracellular matrix breakdown and cleavage of cell adhesion molecules to facilitate immune cell motility, as well as cleavage of the invariant chain during maturation of major histocompatibility complex II. The identification of these diverse specific functions has brought the challenge of delineating cathepsin S activity with great spatial precision, relative to related enzymes and substrates. Here, the development of a potent and highly selective two-step activity based probe for cathepsin S and the application in multicolour bio orthogonal correlative light-electron microscopy is presented. LHVS, which has been reported as a selective inhibitor of cathepsin S with nanomolar potency, formed the basis for our probe design. However, in competitive activity-based protein profiling experiments LHVS showed significant cross-reactivity towards Cat L. Introduction of an azide group in the P2 position expanded the selectivity window for cathepsin S, but rendered the probe undetectable, as demonstrated in bio-orthogonal competitive activity-based protein profiling. Incorporation of an additional azide handle for click chemistry on the solvent-exposed P1 position allowed for selective labelling of cathepsin S. This highlights the influence of click handle positioning on probe efficacy. This probe was utilised in multicolour bio orthogonal confocal and correlative light-electron microscopy to investigate the localisation of cathepsin S activity at an ultrastructural level in bone marrow-derived dendritic cells. The tools developed in this study will aid the characterisation of the variety of functions of cathepsin S throughout biology.